Reversible Underwater Adhesion: The Unique C-shaped Suckers of Net-winged Midge Larvae (Blepharicera sp.) - Guan-Lin Liu (Nature Portfolio, 2020)
Abstract Aquatic insects living in fast-flowing streams have developed various types of attachment systems to resist being carried away by strong currents. Combinations of various attachment devices offer aquatic insects advantages in underwater adhesion on substrates with different surface properties. In this study, the net-winged midge (Blepharicera sp.) larvae were investigated to understand micro-/nano-structural attachment mechanisms. The hierarchical structure of insect adhesive surfaces was characterized using Optical Microscopy (OM), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). Centrifugal measurements were also conducted to measure the critical rotational velocity at which the larvae of Blepharicera sp. can adhere to substrates with varying roughness. Commercial suckers require smooth substrate surface to maintain a pressure that is lower than the surrounding pressure for adhesion under the sucker cup while the suckers of net-winged midge larvae possess hierarchical micro-/nano-structures, which attach closely to rough surfaces underwater. Furthermore, the functions of microstructures observed on the sucker, including wrinkled surface, inward setae, outer fibers, and nick were explored and may contribute to underwater adhesion. The aligned C-shaped suckers can attach and detach effectively by closing or opening the gap. The unique microstructure and adhesion capability of such suckers could shed light on the design and synthesis of novel bio-inspired devices for reversible underwater adhesion.